THE ROLE OF STUDENT MOTIVATION IN THE MODERN EDUCATIONAL PROCESS - Muratova Dilorom Mahmudovna,; Kayratov Nursultan, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation:  Student  motivation  is  one  of  the  most  important  factors  in  the modern  educational  process.  It  has  a  direct  influence  on  academic  performance, learning activity, and the overall development of a student’s personality. In today’s educational environment, where information is easily accessible and teaching methods are  constantly  changing,  motivating  students  becomes  a  key  task  for  educators. This article examines the concept of student motivation, its main types, and effective ways to increase motivation in the learning process. Special attention is given to the role of the teacher, modern teaching methods, and the creation of a positive educational environment that supports students’ interest in learning.